Working-Class Heroes : Protecting Home, Community, and Nation in a Chicago Neighborhood - Kefalas, Maria (Book collections on Project MUSE., 2003)
Chicago's Southwest Side is one of the last remaining footholds for the city's white working class, a little-studied and little-understood segment of the American population. This book paints a nuanced and complex portrait of the firefighters, police officers, stay-at-home mothers, and office workers living in the stable working-class community known as Beltway.